1989
DOI: 10.1039/p19890002463
|View full text |Cite
|
Sign up to set email alerts
|

Diels-Alder reactivity of pyrano[3,4-b]indol-3-ones. Part 4. Synthesis of the carbazole alkaloids carbazomycin A and B and hyellazole

Abstract: The first synthesis of the carbazole alkaloids carbazomycins A and B (1) is described. The key step is the regioselective Diels-Alder reaction between 1 -methylpyrano [3,4-61 indol-3-one (4) and ethyl trimethylsilyl propynoate to give ethyl 1 -methyl-3-trimethylsilylcarbazole-2-carboxylate (6). The ester and trimethylsilyl groups in carbazole ( 6 ) are converted into methyl and methoxy groups respectively, and the final oxygen substituent is introduced, after protection of the carbazole nitrogen, by brominati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…The first oxidative dimerization24,25 of (unnatural) hydroxycarbazoles was found by serendipity, in the course of the synthesis of carbazomycins A ( 17 ) and B ( 18 ),26 which are antibiotic natural products from Streptoverticillium ehimense 27. Carbazomycin B ( 18 ) is the only carbazole for which extensive biogenetic experiments have been performed, leading to a far‐reaching understanding of its biosynthesis 5,28.…”
Section: Synthesis Of Biarylic Biscarbazoles By Non‐stereoselective Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The first oxidative dimerization24,25 of (unnatural) hydroxycarbazoles was found by serendipity, in the course of the synthesis of carbazomycins A ( 17 ) and B ( 18 ),26 which are antibiotic natural products from Streptoverticillium ehimense 27. Carbazomycin B ( 18 ) is the only carbazole for which extensive biogenetic experiments have been performed, leading to a far‐reaching understanding of its biosynthesis 5,28.…”
Section: Synthesis Of Biarylic Biscarbazoles By Non‐stereoselective Cmentioning
confidence: 99%
“…Carbazomycin B ( 18 ) is the only carbazole for which extensive biogenetic experiments have been performed, leading to a far‐reaching understanding of its biosynthesis 5,28. In an attempt to oxidize 3‐hydroxycarbazole 15 to the ortho‐quinone structure 16 by using dibenzoyl peroxide, Moody et al26 obtained the 4,4′‐dimer 19 in high yields (Fig. 3).…”
Section: Synthesis Of Biarylic Biscarbazoles By Non‐stereoselective Cmentioning
confidence: 99%
“…Benzoyl peroxide was utilized by Moody and coworkers to make biscarbazole in 1989. 18 Bringmann and other groups used tert -butyl peroxide to oxidatively introduce the C-C bond from 1-hydroxycarbazoles. 19 Later, Knӧlker reported that tetrachloro- para -benzoquinone produced an axial bond ortho to the hydroxyl group.…”
Section: Introductionmentioning
confidence: 99%
“…(11). (33) was formed and reacted with another alkyne unit (34) to give arylboronate (35). It was subject, without purification, to the Suzuki-Miyaura coupling with aryl iodide (36) in aqueous toluene to afford biaryl compound (37).…”
Section: Iii-3 [2+2+2] Cycloadditionsmentioning
confidence: 99%
“…(17). with electron-deficient dienes such as tetrazines [34] or pyranolones [35]. On the other hand, with electron-rich dienes, the DA reaction requires a stronger electronwithdrawing group on the alkyne, such as in MeO 2 CC CSnBu 3 [36].…”
Section: Iv-2 [4+2] Cycloadditionsmentioning
confidence: 99%